The plant WEE1 kinase is involved in checkpoint control activation in nematode‐induced galls. Issue 1 (30th October 2019) - Cabral, Danila; Banora, Mohamed Youssef; Antonino, José Dijair; Rodiuc, Natalia; Vieira, Paulo; Coelho, Roberta R.; Chevalier, Christian; Eekhout, Thomas; Engler, Gilbert; De Veylder, Lieven; Grossi‐de‐Sa, Maria Fatima; de Almeida Engler, Janice
Summary: Galls induced by plant‐parasitic nematodes involve a hyperactivation of the plant mitotic and endocycle machinery for their profit. Dedifferentiation of host root cells includes drastic cellular and molecular readjustments. In such a background, potential DNA damage in the genome of gall cells is evident. We investigated whether DNA damage checkpoint activation followed by DNA repair occurred, or was eventually circumvented, in nematode‐induced galls. Galls display transcriptional activation of the DNA damage checkpoint kinase WEE1, correlated with its protein localization in the nuclei. The promoter of the stress marker gene SMR7 was evaluated under the WEE1‐knockout background. Drugs inducing DNA damage and a marker for DNA repair, PARP1, were used to understand the mechanisms for coping with DNA damage in galls. Our functional study revealed that gall cells lacking WEE1 conceivably entered mitosis prematurely, disturbing the cell cycle despite the loss of genome integrity. The disrupted nuclei phenotype in giant cells hinted at the accumulation of mitotic defects. In addition, WEE1‐knockout in Arabidopsis and downregulation in tomato repressed infection and reproduction of root‐knot nematodes. Together with data on DNA‐damaging drugs, we suggest a conserved function for WEE1 in controlling G1/S cell cycle arrest in response to a replication defect in galls.